2010
DOI: 10.2176/nmc.50.668
|View full text |Cite
|
Sign up to set email alerts
|

Familial Moyamoya Disease Associated With Graves' Disease in a Mother and Daughter -Two Case Reports-

Abstract: A mother and daughter presented with a rare combination of moyamoya disease and Graves' disease. A 19-year-old woman experienced numbness in her right hand due to cerebral infarction during therapy for Graves' disease. Cerebral angiography demonstrated stenoses of the bilateral internal carotid arteries and net-like abnormal collateral vessels indicative of moyamoya disease. Her 52-year-old mother with a history of Graves' disease presented with left hemiparesis due to intracerebral hemorrhage; she recovered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…The rarity and ethnic heterogeneity suggest that only a few patients with GD are susceptible to moyamoya vasculopathy. The existence of a genetic background linking thyroid disease and intracranial arterial stenosis was also supported by familial cases of moyamoya disease and GD [26]. Interestingly, RNF213 variation has also been shown to be related to intracranial artery stenosis of unknown etiology [25].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The rarity and ethnic heterogeneity suggest that only a few patients with GD are susceptible to moyamoya vasculopathy. The existence of a genetic background linking thyroid disease and intracranial arterial stenosis was also supported by familial cases of moyamoya disease and GD [26]. Interestingly, RNF213 variation has also been shown to be related to intracranial artery stenosis of unknown etiology [25].…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, RNF213 variation has also been shown to be related to intracranial artery stenosis of unknown etiology [25]. The existence of a genetic background linking thyroid disease and intracranial arterial stenosis was also supported by familial cases of moyamoya disease and GD [26]. Thus, in addition to thyroid function and thyroid antibodies, genetic factors are involved in the relationship between thyroid disease and intracranial arterial disease.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests a possible underlying immune process contributing to the development of Moyamoya disease4). In addition, there are familial cases of Moyamoya disease and Graves' disease, indicating hereditary involvement in both diseases14). Taken together, genetic factors and autoimmunity may play important roles in the pathogenesis of the coexistence of Moyamoya disease and Graves' disease6).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that autoimmune mechanisms that worked for the development of Graves’ disease might also play an important role in the onset of Moyamoya disease. Tokimura et al (7) reported one pair of a mother and a daughter who both developed Moyamoya disease and Grave’s disease, and implicated genetic factors because one gene locus of Moyamoya disease (chromosome 8q23, MYMY3) is very close to that of autoimmune thyroid disease (8q23-24). Furthermore, patients with Moyamoya disease may be more likely to have elevated thyroid autoantibodies than those with non-Moyamoya disease strokes (11).…”
Section: Discussionmentioning
confidence: 99%